Exploring Scientific Literacy on Ecosystem Concept Among Eleventh Grade Students in an Indonesia Tahfiz-Based Islamic Senior High School - Salwa Yurinanda Lubis; Ummi Nur Afinni Dwi Jayanti (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: The mastery of science literacy has a very important role in daily life, both for students and society as a whole. Mastery of science literacy provides significant advantages, both at the individual and collective levels. They purpose of this studying as to describe the levels of science literacy ability of high school student on Madrasah Aliyah Tahfizil Qur'an of the North Sumatra Islamic Centre Foundation especially ecosystem materials, both in understanding and mastering scientific concepts related to ecosystems, as well as to assess critical thinking skills, ability to communicate scientific findings, and environmental awareness. Methodology: The method used in this study is to use a type of cross-sectional quantitative research research. The sample used was 60 students with a sampling technique using a total sampling technique. The research instruments us a that studying is an they to if science literacy questions in the form of multiple choices. This study's data analysis methodology employs quantitative descriptive analytic approaches to examine students' science literacy outcomes, which are represented as percentages. Findings: Results obtained on the ability level of second grade students in Madrasah Aliyah Tahfizil Qur'an of the North Sumatra Islamic Centre Foundation is in the medium category, with an average score of 72. This research shows the need for a more relevant learning approach to improve the understanding and application of ecosystem concepts in a scientific context. The importance of integration between the national curriculum and the religious approach applied in madrassas so that students not only understand the concept of science theoretically, but also can apply it in daily life. Contribution: This research is expected to participate in designing more effective science learning strategies in religion-based madrasah schools.